A Population Where Men Live As Long As Women: Villagrande Strisaili, Sardinia - Michel Poulain; Gianni Pes; Luisa Salaris (Journal of Aging Research)
Usually women live longer than men and female centenarians largely outnumber male centenarians. The findings of previous studies identifying a population with a femininity ratio close to 1.0 among centenarians in the mountainous region of Sardinia was the starting point of an in-depth investigation in order to compare mortality trajectories between men and women in that population. The exceptional survival of men compared to women emerges from the comparison with similar Italian data. Age exaggeration for men has been strictly excluded as a result of the age validation procedure. The discussion suggests that besides biological/genetic factors, the behavioral factors including life style, demographic behavior, family support, and community characteristics may play an important role. No single explanation is likely to account for such an exceptional situation and a fully integrated multidisciplinary approach is urgently needed.